METODE EVALUATIF DALAM PROGRAM UPGRADING PERMUKIMAN KUMUH DI INDONESIA - Findara Illa Nursyifa; Ardhya Nareswari (Journal of Architectural Design and Development (JAD), 2025)
Various slum upgrading programs in Indonesia such as KIP, P2KKP, and KOTAKU have been implemented to improve environmental conditions and basic infrastructure. However, the outcomes of these programs show considerable variation, both in terms of physical achievements and their impact on community life. Several studies note that physical improvements are not always followed by behavioral changes or enhancements in residents’ quality of life. This highlights the need for evaluation approaches that assess not only physical aspects but also consider social, economic, and institutional dimensions comprehensively. This study aims to examine various evaluation methods used in previous studies on slum upgrading programs in Indonesia. A systematic literature review was conducted on 18 relevant academic articles, using the PRISMA approach for filtering and bibliographic visualization analysis through VOSviewer. These articles were analyzed based on the evaluation approach used, underlying principles and criteria, and the appropriateness of each method in relation to the location and timing of program implementation. The findings indicate four main types of evaluative approaches: (1) input-output or physical indicator-based, (2) outcome-based, (3) participatory, and (4) context-based. Each approach has its own focus, strengths, and limitations. To address the complex challenges in slum settlements, combining physical and social evaluation approaches is considered more relevant, especially in areas with unique characteristics. Flexible and context-sensitive evaluation methods are essential to ensure that upgrading programs truly benefit communities in the long term.